Minimally invasive computer-assisted repair of feline sacroiliac luxation—a cadaveric study - Wolf, Nicole Diana; Kleiner, Lukas; Precht, Christina; Guevar, Julien; de Preux, Mathieu; Forterre, Franck; Duever, Pia (Frontiers in Veterinary Science, 2025)
IntroductionThe delicate anatomy of the feline sacrum presents challenges for surgeons to perform a safe and accurate surgery without risking to damage vital neurovascular structures. In this context computer-assisted surgery represents an attractive minimally invasive surgical solution to increase the accuracy and safety of the intervention. This cadaveric study evaluates the feasibility and safety of a minimally invasive approach by a novice surgeon using computer navigation compared to traditional fluoroscopy as well as a new method for patient reference array positioning.Material and methodsEleven cats' cadavers were used to simulate sacroiliac joint luxation whereas one had to be excluded due to a sacral fracture. Sides were randomly assigned to two groups: (1) minimally invasive computer-assisted drilling group (MICA group); (2) fluoroscopy-controlled group (FC group). All surgeries were performed by a first-year ECVS resident. After positioning of the reference array, cone beam computer tomography scans were conducted for planning of the temporary and final fixation of the sacroiliac luxation. Final fixation was achieved through a minimally invasive approach via computer-assisted drilling of the iliac wing and the sacral body for the placement of a positional screw (2.4 mm). The other side was operated on via an open dorsal, fluoroscopy-controlled approach. Comparison between the two groups for surgical time, accuracy of screw placement, radiologic safety and the learning curve was recorded. Statistical analysis consisted of Fisher's exact test to compare the assigned radiological safety grades and the Wilcoxon signed-rank test for total surgery time and accuracy.ResultsMean total time for MICA and FC groups were 44 min and 45 s and 19 min and 54 s, respectively. The mean total time for the first five cases was 53 min and 30 s in the MICA group and 20 min and 15 s in the FC group and improved to a mean total time of 36 min and 15 s in the MICA group and to 18 min and 40 s in the FC group in the second five cadavers. Accuracy aberration of surgery in the MICA group improved from a mean deviation on the target point, the end of the drill tract, from 4.2 mm in the first five to 0.9 mm in the second five cats. This criterion was only applicable in the MICA group. Evaluation for radiologic safety was assessed with three radiologic categories (I-III) and four subcategories (a-d). Additionally, the surgery was classified into radiographically safe implant placement (yes/no). The first five cats of the MICA as well as the FC group received a lower safety grade compared to the second five cats. The novel method for placement of the patient reference array was categorized as grade I without violating any vital structures in all 10 cats.DiscussionThe computer-assisted surgery for minimal invasive surgical fixation of sacroiliac luxation seems to be a safe procedure with a steep learning curve. Compared to previous study using the same technical set-up, the safety of the computer-assisted surgical procedure was improved by changing the smooth to the negative threaded pin to have better bone purchase for sufficient anchoring in the spinous process alone and therefore minimizing the risk for violation of the spinal canal.